Combined use of WNT signal pathway inhibitor FH535 and docetaxel causes mitotic catastrophism and antiproliferative effect in non-small cell lung cancer: Docetaxel and FH535 combination in NSCLC - Avşar, Eda Nur; Çetin, İdil (Cellular and Molecular Biology, 2025)
The development of treatment methods used in the treatment of non-small cell lung cancer (NSCLC) is important to prevent problem of increasing mortality. However, the treatment methods used in clinical settings at the clinic are insufficient to eliminate this problem. For this purpose, it was aimed to determine whether the combination of docetaxel (DTX) and FH535 can be used as an anticancer agent candidate in A549 cells and whether it is a candidate drug combination that can be used in clinical treatment after in vivo studies. FH535 is a WNT signaling pathway inhibitor and is known to be overactive in NSCLC. In this study, the effects of DTX and WNT signaling pathway inhibitor FH535 used in NSCLC treatment on A549 and BEAS-2B cell lines were evaluated at the cellular level. While increasing the anticancer activity in A549 cells, the doses showing minimum toxic effect in BEAS-2B cells were determined by Real Time Cell Analysis method. Mitotic activity, BrdU cell proliferation assay and caspase 3,7 activity assay were performed for detailed analysis of the combination dose at cellular level. The results show that the combined dose had an antimitotic effect on A549 cells, causing mitotic catastrophism, while in BEAS-2B cells neither agent was more toxic than either agent alone, reducing mitotic activity and BrdU activity, leading the cell to mitotic catastrophism, while caspase 3,7 activity was unchanged. This study demonstrated for the first time the effects of the combination of DTX and FH535 on A549 and BEAS-2B cell lines.